Evaluation Of Land Resource For Development Of Sorgum Plants In The Pantai Gemi Village District Stabat - Risnawati; Mukhtar Yusuf; Rini Susanti (Talenta Publisher, 2020)
The purpose of this study is to find the location of the land that is suitable or appropriate for sorghum plants seen at the level of the land suitability class are grouped in 5 classes of suitability, namely S1 (highly suitable), S2 (quite appropriate), S3 (marginal suitable), N1 (not appropriate at this time), and N2 (not as permanent). The results of the external scientific minimum in accredited national journals which have an ISSN, the results of the research done to get that to plant sorghum can be developed in fields of agricultural village beach gemi district stabat Kabupaten langkat with attention to some aspects of (1) the availability of excessive water can be done making drainage and (2) retention of nutrients; pH that is slightly sour can be improved by the administration of lime sedangkann low C organic can be corrected with the provision of organic matter can improve the nutrient content increased in the soil.